Going with the flows: New borrowing, debt service and the transmission of credit booms - Mathias Drehmann; Mikael Juselius; Anton Korinek (Bank of Finland, 2018)
Traditional economic models have had difficulty explaining the non-monotonic real effects of credit booms and, in particular, why they have predictable negative after-effects for up to a decade. We provide a systematic transmission mechanism by focusing on the flows of resources between borrowers and lenders, i.e. new borrowing and debt service. We construct the first cross-country dataset of these flows for a panel of house-hold debt in 16 countries. We show that new borrowing increases economic activity but generates a pre-specified path of debt service that reduces future economic activity. The protracted response in debt service derives from two key analytic properties of credit booms: (i) new borrowing is auto-correlated and (ii) debt contracts are long term. We confirm these properties in the data and show that debt service peaks on average four years after credit booms and is associated with significantly lower output and higher crisis risk. Our results explain the transmission mechanism through which credit booms and busts generate non-monotonic and long-lasting aggregate demand effects and are, hence, crucial for macroeconomic stabilization policy.
URN:NBN:fi:bof-201804241458
Keywords: E17; E44; G01; D14; 330